The Old Testament speaks ; v. 5 God's Word for a former generation explained for today's people - Fleming, Donald C. (Kowloon, Hong Kong Living Books for All, 1979)
Contents : v. 5 : Psalms.
Brethren writer. Donated by the author.
Keywords: Bible. O.T. -- introductions